2023
DOI: 10.1021/acs.est.3c00456
|View full text |Cite
|
Sign up to set email alerts
|

Destabilizing Effects of Environmental Stressors on Aquatic Communities and Interaction Networks across a Major River Basin

Abstract: Human-driven environmental stressors are increasingly threatening species survival and diversity of river systems worldwide. However, it remains unclear how the stressors affect the stability changes across aquatic multiple communities. Here, we used environmental DNA (eDNA) data sets from a humandominated river in China over 3 years and analyzed the stability changes in multiple communities under persistent anthropogenic stressors, including land use and pollutants. First, we found that persistent stressors s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“… 66 , 67 Interestingly, a recent study of river food-web structure also showed decreased network modularity and negative:positive cohesion under persistent anthropogenic stressors. 68 Thus, our results suggest that the hypersaline lake ecosystem may be more vulnerable to environmental disturbances and may show stronger responses to climate changes in the coming decades.…”
Section: Discussionmentioning
confidence: 69%
“… 66 , 67 Interestingly, a recent study of river food-web structure also showed decreased network modularity and negative:positive cohesion under persistent anthropogenic stressors. 68 Thus, our results suggest that the hypersaline lake ecosystem may be more vulnerable to environmental disturbances and may show stronger responses to climate changes in the coming decades.…”
Section: Discussionmentioning
confidence: 69%
“…This decline has prompted the emergence of the “Kunming-Montreal Global Biodiversity Framework,” which underscores the need for innovative biomonitoring approaches to bolster conservation efforts and enhance environmental management [ 2 ]. Complete taxonomic groups (from bacteria to fishes) and their multiple organization levels (from population to food web) all contribute to the functions and stability of the aquatic ecosystem and, thus, should be monitored conclusively [ 3 , 4 ]. These new monitoring demands cannot be met by morphology-based biomonitoring methods alone, and there is an urgent need for reliable methods capable of detecting diverse taxonomic groups to ensure accurate biodiversity assessments [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%